2013
DOI: 10.1007/s13679-013-0051-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Energy Intake, and Obesity: The Links Between Exercise and Appetite

Abstract: Overweight and obesity are often theorized using the energy balance equation. When energy intake (EI) is greater than energy expended this creates a positive energy balance and leads to weight gain, conversely when energy expenditure (EE) exceeds EI this creates a negative energy balance and weight loss. Physiologists have been examining the relationship between EE and EI since the 1950s. Total daily EE is comprised of two main components; resting metabolic rate (RMR) and physical activity (PA). This review wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 55 publications
0
10
0
1
Order By: Relevance
“…While the beneficial effects of physical activity (PA) on many obesity-related diseases such as diabetes, cardiovascular disease, and certain cancers are well established (3)(4)(5), the effectiveness of PA on weight status, and particularly its capacity to promote weight loss, remains under debate (6). Energy balance, and ultimately weight loss and weight gain, is a direct result of dietary energy intake and energy expenditure (7,8). As PA represents the only component of energy expenditure that is driven directly by behavior and therefore is its most variable contributor (9), it is critical to understand the impact of PA on food intake and particularly whether increased PA invokes a compensatory effect on food intake which could negate beneficial effects of PA on weight status (10).…”
Section: Introductionmentioning
confidence: 99%
“…While the beneficial effects of physical activity (PA) on many obesity-related diseases such as diabetes, cardiovascular disease, and certain cancers are well established (3)(4)(5), the effectiveness of PA on weight status, and particularly its capacity to promote weight loss, remains under debate (6). Energy balance, and ultimately weight loss and weight gain, is a direct result of dietary energy intake and energy expenditure (7,8). As PA represents the only component of energy expenditure that is driven directly by behavior and therefore is its most variable contributor (9), it is critical to understand the impact of PA on food intake and particularly whether increased PA invokes a compensatory effect on food intake which could negate beneficial effects of PA on weight status (10).…”
Section: Introductionmentioning
confidence: 99%
“…There has been increasing interest in the relationship between physical activity and appetite control, as both play an integral part in energy balance (e.g. [37]). Regular physical activity and exercise training are associated with several physiological adaptations, such as improved insulin sensitivity [8], leptin sensitivity [9, 10], blood pressure [11], blood lipids [12], substrate metabolism [13] and body composition [14], some of which have been proposed as mechanisms involved in eating behaviour [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…However, increasing exercise and therefore, energy expenditure, does not always result in desired weight loss. In a recent review, Caudwell, Gibbons, Finlayson, Naslund, and Blundell (2013) reported that, although the research predominantly shows an acute bout of exercise does not create an increase in hunger, desire to eat, or energy intake, when exercise is extended over a few days and caloric intake is monitored for a longer period, partial compensation for increased energy expenditure can occur. In these cases, even though individuals are increasing physical activity, they are subsequently increasing #0# caloric intake thereby undermining their own weight loss efforts.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, even though individuals are increasing physical activity, they are subsequently increasing #0# caloric intake thereby undermining their own weight loss efforts. High-intensity exercise is correlated with a transient reduction in hunger that may be due to a temporary decrease in the active component of the appetitestimulating hormone ghrelin (Caudwell et al, 2013). The appetite-regulating hormones acylated ghrelin, leptin, GLP-1, and PYY 3-36 are recognized to be a major influence on energy homeostasis (Klok, Jakobsdottir, Drent, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation